Pengaruh karakteristik perusahaan terhadap pengungkapan akuntansi sumber daya manusia - Istiawan , Agus; Kartika, Andi (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to examine the effect of firm size, profitability, firm age, product diversification, ownership concentration on HR accounting disclosures in banking companies in Indonesia. The study used quantitative descriptive methods. The sample in this study, namely banking companies listed on the Indonesia Stock Exchange and publishing company financial statements consistently for 3 consecutive years, from 2018 to 2020. The analysis technique used in this study is multiple regression with the SPSS test tool. The results of the study indicate that firm size has a significant positive effect on HR accounting disclosures, profitability has a significant positive effect on HR accounting disclosures, company size has a significant positive effect on HR accounting disclosures, product diversification has a significant positive effect on HR accounting disclosures, ownership structure has a significant positive effect on HR accounting disclosures. HR accounting disclosures.